Body composition and lung function in 6 to 12 yr old children with cystic fibrosis. (29th September 2015) - Williams, J; Benden, C; Suri, R; Jaffe, A; Fewtrell, M
Abstract : Objective: Patients with cystic fibrosis (CF) are at risk of malnutrition and studies have reported associations between lower fat-free mass (FFM) and poor lung function (LF). The authors used the "gold standard" four-component model (4CM) to assess body composition (BC) and related the findings to LF. Methods: BC was measured using the 4CM in 85 CF subjects aged 6–12 years, and results compared with (1) UK reference data; (2) data from healthy age and sex matched controls. LF (forced expiratory volume in 1 sec; FEV1 % predicted) was measured in patients and relationships with fat mass (FM) and FFM adjusted for height (FM and FFM indices (FMI and FFMI)) investigated. Results: Compared to UK reference data, boys with CF (n=37) were shorter; (mean (SD) height SD scores (sds); −0.5 (1.0), p<0.05) but had higher BMI sds; (0.4 (1.0) p<0.01); girls with CF were shorter; (−0.6 (1.0) p<0.001) and had lower BMI sds; (−0.3 (1.0), p<0.05). Compared to matched controls, CF boys had greater FFMI sds; (0.6 (1.0), p<0.01) while CF girls had lower FMI sds; (−0.7 (0.9), p<0.001) and mineral mass index sds; (−0.8 (1.1), p<0.001); the mineral deficit was not apparent in prepubertal girls (n=24). Six children (5 boys) had BMI sds >1.64 (95th centile); this was due to increased FM in four boys only. CF girls had lower FEV1% predicted than boys (mean (SD) 77.6 (18.4) vs 91.3 (20.9); p<0.01). FM was significantly related to FEV1 in girls only (p<0.01) but there was no association between FFM and LF in either sex. Conclusion: Using the gold standard 4CM, CF boys had normal BC, while CF girls had lower FM than controls even after adjusting for size. Six children had a BMI sds in the obese range but in two cases this was due to high FFM, not FM. In contrast to previous studies we found no association between FFM and LF. The significant positive association between FM and FEV1 in girls only may reflect the poorer nutritional status of the girls, even at this young age. Given that prognosis is worse in girls, this sex difference merits more attention.